2015
DOI: 10.1590/2176-9451.20.1.097-107.oar
|View full text |Cite
|
Sign up to set email alerts
|

Alternative treatment for open bite Class III malocclusion in a child with Williams-Beuren syndrome

Abstract: Williams-Beuren syndrome (WBS) is a rare genetic condition that affects approximately 1 in every 20,000 - 50,000 live births. WBS children have specific skeletal deformities, dental malformations and rare lingual muscle dysfunction. The need for orthodontic and orthognathic therapy has arisen and has been considered a real clinical challenge even for experienced professionals, once it requires a complex and individualized treatment plan. This study reports a case of orthopedic expansion of the maxilla, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This alteration was present in 16 patients (94.12%), while dental midline deviation and high-arched palate was detected in 11 and 9 patients, respectively. Indeed, malocclusion is one of the most frequent common oral problems among the morphological and functional disorders of the orofacial complex in patients with WBS ( 14 , 15 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…This alteration was present in 16 patients (94.12%), while dental midline deviation and high-arched palate was detected in 11 and 9 patients, respectively. Indeed, malocclusion is one of the most frequent common oral problems among the morphological and functional disorders of the orofacial complex in patients with WBS ( 14 , 15 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Therefore a rigid and multidisciplinary management plan is required in the treatment of dental problems in WS. 16 Because the patients with WS have overall IQ of 50-60 range, mental retardation and restricted visual ability, poor oral hygiene is observed as a major problem among these patients. 12,15,17,18 For that, a low degree of oral hygiene and enamel hypoplasia defects cause caries, gingival problems and halitosis in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Few case reports of orthodontic treatment in WBS can be found in the literature, which could be attributed to the varying degree of cooperation provided by the patient and family in response to orthodontic treatment. Vieira et al [ 10 ] reported a case of a patient with WBS who received orthodontic treatment with satisfying results. The patient received orthopedic expansion of the maxilla, in which a modified facial mask was used to protract the maxillary complex associated with clockwise rotation of the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oral and facial characteristics, WBS patients may present with microdontia, generalized diastemas, anodontia, caries, enamel hypoplasia, dental malocclusion, atypical deglutition, and counterclockwise rotation of the maxilla accompanied by a retruded mandible [ 10 ]. The present case had a Class III malocclusion associated with a cleft palate and dental agenesis.…”
Section: Discussionmentioning
confidence: 99%